A review on thromboprophylaxis in pregnancy - Chow, T.W.; Wong, Y.M. (Malaysian Medical Association, 2001)
Thromboembolic disease remains an important cause of maternal mortality worldwide. The risk assessments for prevention of thromboembolism in pregnancy are controversial due to lack of large-scale randomised controlled trials. Unfractionated heparin is at present, the anticoagulant of choice during pregnancy. However, it may be superseded by low-molecular-weight heparin in the near future because of its safety and efficacy.